Factors That Influence the Quality of Human Resources on Employee Performance at UPT Puskesmas Sitinjo Dairi Regency in 2023 - Ruth Damayanthy Br Girsang; Fikarwin Zuska; Nettietalia Brahmana (Jurnal Info Sains : Informatika dan Sains, 2023)
One way to improve how well a company or institution does its job is to improve its Human Resources (HR). So, high-competence human resources are needed because expertise or competence can help improve both the performance of the company and the performance of the employees themselves. The goal of this study was to find out how HR quality factors affect how well employees do their jobs. The research was carried out at UPT Puskesmas Sitinjo. There were 49 employees at UPT Puskesmas Sitinjo, and those 49 employees made up the group for this study. A questionnaire was used as a study tool to get the information needed, and multiple linear regression was used to look at the information. The study shows that a) intellectual abilities, knowledge, and skills, as well as leadership, have some effect on employee performance, and b) intellectual abilities, knowledge, and skills, as well as leadership, have an effect on employee performance at the same time. From the results of this study, it is hoped that the management of the Community Health Center will give all of the people who work there a chance to go to training or get a better education than what is currently available and put people in jobs that match their skills.